2004
DOI: 10.1056/nejmoa031314
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Mitochondrial Activity in the Insulin-Resistant Offspring of Patients with Type 2 Diabetes

Abstract: BACKGROUND-Insulin resistance appears to be the best predictor of the development of diabetes in the children of patients with type 2 diabetes, but the mechanism responsible is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

91
1,566
15
21

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,967 publications
(1,693 citation statements)
references
References 46 publications
91
1,566
15
21
Order By: Relevance
“…While glucose-6-phosphate can observed in the 31 P-MR spectrum, 13 C-MRS gives access to glycogen and glucose, especially in connection with an infusion of 13 C-enriched [1-13 C]glucose. A sequential acquisition of 1 H-and 31 P-MR spectra in muscle and liver allows for an observation of IMCL, intrahepatic lipids (IHCL) and oxidative phosphorylation (135,136). In principle, combinations of such examinations could take place within the same session, i.e.…”
Section: Combination Of 1 H-mrs Of Imcl and Other Mrs Techniquesmentioning
confidence: 99%
“…While glucose-6-phosphate can observed in the 31 P-MR spectrum, 13 C-MRS gives access to glycogen and glucose, especially in connection with an infusion of 13 C-enriched [1-13 C]glucose. A sequential acquisition of 1 H-and 31 P-MR spectra in muscle and liver allows for an observation of IMCL, intrahepatic lipids (IHCL) and oxidative phosphorylation (135,136). In principle, combinations of such examinations could take place within the same session, i.e.…”
Section: Combination Of 1 H-mrs Of Imcl and Other Mrs Techniquesmentioning
confidence: 99%
“…When mitochondrial activity was determined per muscle weight (i.e. muscle oxidative capacity), studies have either shown no differences [3][4][5] or a lower [6][7][8][9][10][11][12] mitochondrial activity in insulin-resistant participants. Studies that have related mitochondrial activity to markers of mitochondrial volume (intrinsic mitochondrial activity) have either shown a lower [6,12,13] or no difference [9-11, 14, 15] in mitochondrial activity in insulin-resistant participants.…”
Section: Introductionmentioning
confidence: 99%
“…6 Indeed, it has been shown that mitochondrial ATP production in skeletal muscle is impaired in insulin-resistant offspring of patients with type 2 diabetes, 7 which raises the possibility that mitochondrial oxidative phosphorylation in skeletal muscle might be impaired in MetS. However, it has not been determined whether lower aerobic capacity is associated with skeletal muscle dysfunction in these patients.…”
Section: Introductionmentioning
confidence: 99%